A study on the mass-production viability of palwood as an alternative construction material for purlins and wall framing - Cua, John Randolf L.; Espenilla, Leonardo Nestor F.; Lapid, Jose Miguel S.; Molina, Anton Josef M. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Dubbed as the "tree of life," it comes as no surprise that the Philippine government and private companies continue to find ways to promote the growth and development of the coconut industry in the country due to the endless list of products and by-products that can be derived from various parts of the tree. Palwood Manufacturing Corp. (PMC) is a startup company based in Zamboanga de! Norte that manufactures wooden handicrafts. The late owner, Noel Beira, is the inventor of Pa/wood --- an engineered wood composed mainly of coconut fronds that aims to be an alternative construction material stronger and cheaper than majority of its competitors. The goal of the feasibility study is to determine whether or not the company should include Palwood in its line of products. The Philippines has 3.55 million hectares of coconut farmland, approximately 45% of which can be found in Mindanao. Developers and contractors in Mindanao that take part in low-cost housing projects are the target market. The 2014 Low-cost Housing demand according to Housing and Urban Development Coordinating Council (HUDCC) in Visayas-Mindanao is 2,813,868. Analysis of material properties show that the wood may be utilized as purlins and wall framing. Costs show that Palwood is superior to coco lumber in terms of strength and steel in terms of price. Cost analysis also shows that it is more beneficial to directly target the developers instead of going through a distributor first A five-year sales forecast is also generated. Of the total estimated demand, 267,619 units of wall framing and 3,392 units of purlins will be covered by Palwood. Palwood is made up of coconut fronds, binders, and hardeners. Coconut fronds are the stiff midribs of the coconut leaves and is the major component of Palwood. These are to be acquired from nearby coconut plantations. Binders are used to bind the frond fibers to form the desired wood. The hardener, on the other hand, is a highly penetrative solution of selected resins in solvent which soaks deep into the fibers of decaying wood and dries to leave the wood hard and resistant to further moisture penetration. Both are to be acquired from chemical laboratories in Davao City. All machines needed for the production of Palwood are already owned except for the strander machine which costs PhP 899, 400. A total investment expenditure of PhP 1,000, 000 is needed to cover the initial expenses. The project will be financed fully through equity. Based on the financial projections, financial ratios are computed to prove that the company is a good investment and will be financially stable in its operations. Return of Assets (ROA) is equal to Return on Equity (ROE) since all products manufactured for the year are also sold by the end of the year. The Operating Profit Margin (OPM) and Net Profit Margin (NPM) return favorable values. The Earnings Per Share (EPS) show that the company is generating increasing income per year. Finally, Total Asset Turnover (TAT) yields a positive value which shows that Palwood will be able to use its assets well to generate sales. Palwood is also proven to be socially attractive and economically feasible through Cost-Benefit Analysis. The NPV, which is used to measure the net present value of the projected costs and benefits on the community, is Php 17,535, 047.38. This means that the construction of the product and the operation of the company is profitable for the investment to be made. On the other hand, the Total Cost-Benefit Ratio of the company using a discount rate of i = 15% is 4.04 which shows that the project is practical to pursue. Given the aforementioned findings in the marketing, technical, organizational, financial and social aspects, the project was found to be completely feasible and should be pursued.
Submitted in partial fulfillment of the course requirements in IE 153 : Project development and management.
Keywords: Wood, Compressed; Lumber trade -- Philippines; Feasibility studies